Le cognac : entre identité nationale et produit de la mondialisation - Eudes Girard (Cybergeo)
Cognac is a prestigious sort of brandy well-known all over the world which is produced in the French wine-growing region of Charentes. This article explores the history of this production from its medieval origins until the limits of the large districts of production were set, with their own types of crus different in quality and worth, resulting in a specific “geographical cognac region”. The history of this brandy is also linked to an area where prominent national figures such as Jean Monnet and François Mitterrand were born and bred. The purpose of this article is thus to outline a social and cultural geographical survey of cognac that would be worth developing. Lastly, the produce of a typical region bearing the stamp of French identity, cognac is also the resulting product of globalization – 97% of the production volume is exported – the major evolutions of the cognac market being tightly connected to the great socioeconomic and sociocultural shifts of this world.